Dilemmas Managing Doubt about Family Members' Health Complaints: A Normative Approach. Issue 3 (2nd July 2020) - Thompson, Charee M.; Parsloe, Sarah; Acevedo Callejas, Michelle
ABSTRACT: Uncertainty is inherent to the illness experience; for those who are not ill themselves, the inability to directly access another person's embodied experiences can heighten feelings of uncertainty. Doubt about the extent to which others are ill is a common and consequential form of partner uncertainty that we focus on in this study. Guided by Goldsmith's (2001, 2004, 2016) normative framework, we analyzed data from interviews with 32 individuals ( M age = 35.28, SD = 9.91; 72% female), uncovering how participants struggled to manage their doubt of family members' health and to respond in normatively supportive ways to family members' health claims. Each uncertainty management strategy for seeking and avoiding information, obtaining social support, and adjusting to chronic doubt often risked valued identities and relationships. This study illuminates the underrepresented perspective of individuals who doubt family members' health issues and the challenges they face as support providers.